Narrating forest loss: Ecological violence and environmental silence in a comparative study of Jejak Balak and Supernova: Partikel - Heru S. P. Saputra; Hery Prasetyo; Sainul Hermawan; Titik Maslikatin; Edy Hariyadi (Universitas Ahmad Dahlan, 2026)
This comparative study examines the representation of ecological violence and the function of environmental silence in Jejak Balak (Traces of Logging) by Ayu Welirang and Supernova: Partikel (Supernova: Particle) by Dee Lestari within Indonesia’s structurally driven deforestation crisis. Literature not only reflects ecological degradation but also shapes its meaning through narratives that simultaneously expose and obscure violence against forests. Using an interpretive qualitative approach grounded in ecocriticism and informed by political ecology and the concept of slow violence, this study analyzes how ecological meaning is constructed in the two novels. The findings show that Jejak Balak depicts forest exploitation explicitly through socio-economic conflicts, while Supernova: Partikel renders ecological crisis in a more reflective and spiritual mode. In both texts, the marginalization of forest voices and long-term ecological impacts reveals environmental silence as a key narrative mechanism. This study advances ecocritical scholarship by demonstrating that environmental silence is not merely an aesthetic absence but a structuring principle that shapes how ecological violence is perceived and potentially normalized. It concludes that contemporary Indonesian literature contributes to the formation of ecological ethics through both representation and silence.